2007
DOI: 10.1029/2006tc001987
|View full text |Cite
|
Sign up to set email alerts
|

Active tectonics of the Beichuan and Pengguan faults at the eastern margin of the Tibetan Plateau

Abstract: The steep, high‐relief eastern margin of the Tibetan Plateau has undergone rapid Cenozoic cooling and denudation yet shows little evidence for large‐magnitude shortening or accommodation generation in the foreland basin. We address this paradox by using a variety of geomorphic observations to place constraints on the kinematics and slip rates of several large faults that parallel the plateau margin. The Beichuan and Pengguan faults are active, dominantly dextral‐slip structures that can be traced continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
324
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 364 publications
(350 citation statements)
references
References 34 publications
(90 reference statements)
14
324
1
2
Order By: Relevance
“…We resolve no significant shortening on the Wenchuan fault, based on the mapped geometries and the fault and its cutoff relationships. The activity of this fault is unclear: Burchfiel et al (1995) identified active dextral slip, while Densmore et al (2007) found no unambiguous evidence for Quaternary displacement in their field studies.…”
Section: Crustal Shortening and Topography Of The Longmen Shanmentioning
confidence: 98%
See 2 more Smart Citations
“…We resolve no significant shortening on the Wenchuan fault, based on the mapped geometries and the fault and its cutoff relationships. The activity of this fault is unclear: Burchfiel et al (1995) identified active dextral slip, while Densmore et al (2007) found no unambiguous evidence for Quaternary displacement in their field studies.…”
Section: Crustal Shortening and Topography Of The Longmen Shanmentioning
confidence: 98%
“…Exhumation rates imply that the present relief of the mountain belt has largely formed since the Miocene (Kirby et al, 2002). However, geodetic studies (Chen et al, 2000;Shen et al, 2005;Meade, 2007), as well as geologic and geomorphic observations (Densmore et al, 2007), generally agreed prior to the Wenchuan earthquake that east-west shortening across the range and within the basin was very limited (< 3 mm=yr). These studies also indicate an important component of strike-slip deformation, at least since 10-15 ka.…”
Section: Tectonic Setting Of the Wenchuan Earthquake In The Longmen Shanmentioning
confidence: 98%
See 1 more Smart Citation
“…Among these, the long-term vertical slip rate of the BeichuanYingxiu fault, the middle segment of the mountain-central fault, is 1-2 mm/a, and the inferred vertical slip rate of the Longmenshan thrust belt as a whole is as high as 4-6 mm/a [11][12][13]. The NW-trending crustal shortening rate across the Longmenshan thrust belt is inferred by geological study to be 10 mm/a [14], and the balance geological cross-section shows that its total crustal shortening amount is as high as 40%-60% [15].…”
Section: Tectonic Setting In Briefmentioning
confidence: 99%
“…The Lushan earthquake occurred along the southern segment of the Longmenshan thrust belt, where there are NE-striking and NW-dipping imbricate reverse faults, namely, from northwest to southeast, the Gengda-Longdong, YanjingWulong, Shuangshi-Dachuan and Dayi faults ( Figure 2). Similar to the tectonic origin of the Wenchuan earthquake [3,26], the Lushan earthquake is considered to be originated from an abrupt slip on a low angle reverse fault of the southern segment of the Longmenshan thrust belt between the Bayan Har Block and South China Block, where local crustal shortening has been dominated as a result of the Bayan Har Block moving southeastward and colliding with the South China Block [3, [10][11][12][13][14][15][16]. Due to the fact that the epicenter of the Lushan earthquake was located at the site where the Coulomb stress increment was calculated by occurrence of the Wenchuan earthquake [5,6], we thus consider that this Coulomb stress increment may have potentially hastened the occurrence of the Lushan earthquake on a critically stressed reverse fault.…”
Section: Tectonic Setting In Briefmentioning
confidence: 99%